Nanoindentation in Materials Science - Nemecek, Jiri (IntechOpen, 2012)
Nanotechnologies have already attracted massive interest in multiple fields of science and industry. In the past decades, we have witnessed the progress in micro-level experimental techniques that revolutionize the material science. Designing new materials based on the knowledge of mechanics of their building blocks and microstructure manipulations at nanometer scale have become a reality. Nanoindentation, as a leading micro-level mechanical testing technique, has attracted wide attention in numerous research fields and applications. Nowadays, an extensive variety of testing areas ranging from classical thin coatings in machinery engineering, electronics and composites to far fields of civil engineering, biomechanics, implantology or even agriculture can be covered with this universal testing tool. The book aims to be a walk through achievements in some of the distant fields and to give a brief overview of the current frontiers in nanoindentation. Although it is not possible to cover the whole width of the possible themes in one book, it is believed that the reader will benefit from the topics variety and the book will serve as a useful source of literature references.